Intraductal papillary mucinous neoplasm (IPMN) with high-grade dysplasia is a risk factor for the subsequent development of pancreatic ductal adenocarcinoma. Issue 3 (March 2016) - Rezaee, Neda; Barbon, Carlotta; Zaki, Ahmed; He, Jin; Salman, Bulent; Hruban, Ralph H.; Cameron, John L.; Herman, Joseph M.; Ahuja, Nita; Lennon, Anne Marie; Weiss, Matthew J.; Wood, Laura D.; et al.
Abstract: Background: Non-invasive intraductal papillary mucinous neoplasm (IPMN) with high-grade dysplasia and IPMN-associated invasive pancreatic ductal adenocarcinoma (PDAC) are frequently included under the term "malignancy". The goal of this study is to clarify the difference between these two entities. Methods: From 1996 to 2013, data of 616 patients who underwent pancreatic resection for an IPMN were reviewed. Results: The median overall survival for patients with IPMN with high-grade dysplasia (92 months) was similar to survival for patients with IPMN with low/intermediate-grade dysplasia (118 months, p = 0.081), and superior to that of patients with IPMN-associated PDAC (29 months, p < 0.001). IPMN-associated PDAC had lymph node metastasis in 53%, perineural invasion in 58%, and vascular invasion in 33%. In contrast, no lymph node metastasis, perineural or vascular invasion was observed with high-grade dysplasia. None of the patients with IPMN with high-grade dysplasia developed recurrence outside the remnant pancreas. In stark contrast 58% of patients with IPMN-associated PDAC recurred outside the remnant pancreas. The rate of progression within the remnant pancreas was significant in patients with IPMN with high-grade (24%) and with low/intermediate dysplasia (22%, p = 0.816). Conclusion: Non-invasive IPMN with high-grade dysplasia should not be considered a malignant entity. Compared to patients with IPMN with low/intermediate-grade dysplasia, those with high-grade dysplasia have an increased risk of subsequent development of PDAC in the remnant pancreas.